ELASTIC STRAIN DISTRIBUTION IN ONE LAYER QUANTUM RING SUPERLATTICE - Mughnetsyan, V.N.; Kirakosyan, A.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
The elastic strain distribution in one layer InAs/GaAs quantum ring superlattice is calculated using the Green function method. The dependencies of the strain tensor components on spatial coordinate in three different directions are obtained. The comparison of the obtained results with ones for a single quantum ring shows that the effect of the matrix material on the strain distribution inside the ring is more pronounced in the case of single quantum ring. The behavior of the strain tensor components in different directions is strongly different both for the single quantum ring and quantum ring superlattice due to the anisotropy of the crystal lattice.